Modified Potato Starch as a Potential Retardant for Prolonged Release of Lidocaine Hydrochloride from Methylcellulose Hydrophilic Gel - Justyna Kobryń; Bartosz Raszewski; Tomasz Zięba; Witold Musiał (MDPI AG, 2023)
The problem of drug delivery often concentrates on the prolongation of drug activity. Application of natural polymers which are biodegradable and inexpensive is in the interest of many researchers. The aim of this study was the application of newly synthesized starch derivatives as potential functional excipients proposed for hydrophilic gel with lidocaine hydrochloride (LH) to prolong drug release from the hydrogel matrix. In our study, we investigated the effect of starch modified with citric acid on the release kinetics of LH using UV-VIS and Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), as well as viscosity and pH measurements. We demonstrated the effectiveness of citric-acid-modified starch in prolonging the release of LH from methylcellulose gel.